UTILIZING 3D MAPPING PHOTOGRAMMETRY AND AIRFEEL WEATHER MONITORING FOR SOLAR AND WIND POWER PLANT DEVELOPMENT PLANNING ON GILI IYANG - Megantoro, Prisma; Apsari, Retna; Nurrohma Hidayah, Nayu; Ananta Sari, Feby; Rania Khadijah, Alyssa; Dwi Cahyono, Heru; Abdilah, Waldi; Uta Nugraha, Yoga; Jamilatul Awalin, Lilik; Syahril Mubarok, Muhammad (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
This article discusses community service activities on Gili Iyang Island, Sumenep, Madura, which focus on implementing appropriate technology in sensing the potential of renewable energy sources. Gili Iyang Island itself is an area that actively encourages the use of renewable energy. In this activity, maintenance and monitoring of data on AirFeel are carried out, including device checks and monitoring data accuracy levels through periodic calibration. Airfeel is used as a weather station to measure the potential of renewable energy, especially wind and solar energy. The potential for wind energy is considered from the speed and direction of the wind, while the potential for solar energy is considered from the level of solar irradiation. These parameters allow Airfeel to determine the optimal location for renewable energy generation based on weather conditions. Additionally, the DJI Phantom 4 Pro RTK drone was used for 3D Mapping Photogrammetry. This technology aids in creating three-dimensional maps that are considered in the planning and development of renewable energy power plants at the location. Implementing these two technologies can contribute to future planning for developing other renewable energy sources in Gili Iyang Island.